A survey of ethyl carbamate in beer from Chinese market. (September 2017) - Li, Guohui; Zhong, Qiding; Wang, Daobing; Gao, Hongbo
Abstract: Result of a survey of ethyl carbamate (EC) in beer was carried out by gas chromatography-mass spectrometry (GC/MS). 217 samples were purchased from supermarkets in five cities of China. The concentrations of EC ranged from n.d. to 19.6 μg/kg with an average level of 2.2 μg/kg, and positive rate was 95.4%. Mean in domestic beer (N = 142, incidence 97.3%) was 1.8 μg/kg, lower than the 2.9 μg/kg in imported beer (N = 75, incidence 94.4%). The result of domestic beer showed that EC level in canned beer (N = 73, mean = 1.5 μg/kg) was lower than that in bottled beer (N = 69, mean = 2.1 μg/kg). Additionally, EC level of beer from different countries was varied. Furthermore, a strong positive correlation of EC content in beer with alcohol content, storage time, temperature and light exposure was observed. Highlights: A survey of level of EC in beer form Chinese markets was carried out. Mean of domestic beer was lower than that of imported beer. The EC level of canned beer was lower than that of bottled beer. EC level of beer in different countries varied obviously. Positive correlation of EC content with alcohol content and storage conditions.